2014
DOI: 10.1097/iae.0b013e3182a48917
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Morphologic Changes and Concentrations of Cytokines in Eyes With Diabetic Macular Edema

Abstract: The significant association of SRD with intravitreal IL-6 indicates that inflammation may play an important role in the development of SRD in diabetic macular edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
96
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 38 publications
7
96
1
2
Order By: Relevance
“…In particular, inflammatory cytokines may have more important roles than VEGF in eyes with DMO resistant to serial anti-VEGF injections; past studies have shown that although VEGF is correlated with the severity of diabetic retinopathy, no significant correlation was shown between VEGF level and DMO, whereas inflammatory factors such as IL-6 and MCP-1 have shown significant correlation with DMO. [33][34][35][36][37] This may explain the favorable morphological improvement in our study of CT and CFT to IVD, in eyes with refractory DMO.…”
Section: Discussionsupporting
confidence: 49%
“…In particular, inflammatory cytokines may have more important roles than VEGF in eyes with DMO resistant to serial anti-VEGF injections; past studies have shown that although VEGF is correlated with the severity of diabetic retinopathy, no significant correlation was shown between VEGF level and DMO, whereas inflammatory factors such as IL-6 and MCP-1 have shown significant correlation with DMO. [33][34][35][36][37] This may explain the favorable morphological improvement in our study of CT and CFT to IVD, in eyes with refractory DMO.…”
Section: Discussionsupporting
confidence: 49%
“…Levels of IL-6 were shown to be increased in the eyes of patients with DR, particularly in proliferative stages of the disease [32, 33]. Recently, higher concentrations of inflammatory cytokines in the vitreous and aqueous humor have been reported in eyes with SRD, thus suggesting the presence of a significant inflammatory component [5, 9, 10, 30]. Indeed, high serum IL-6 level was found to be associated with severe grades of DR itself [11].…”
Section: Discussionmentioning
confidence: 99%
“…The main contributor to DME development has been thought to be the intraocular production of proinflam matory cytokines such as IL-6, IL-8, TNF-α, IL-1β, VEGF, pigment epithelium-derived factor, ICAM-1, and monocyte chemotactic protein (MCP-1) [9, 10, 24, 25]. There are very few data with regard to the altered levels of inflammatory mediators in peripheral blood of DME patients, in contrast to those mediators in intraocular blood [9, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients with DME, those with serous subretinal detachment have the worst visual prognosis after therapy and this seems to be related to the interruption of ELM and EZ zones [29] . ELM disruption with subsequent microglial cell attraction has been hypothesized, and this could explain the higher concentration of intravitreal inflammatory cytokines in eyes with subretinal detachment [30] . Different patterns of increased foveal fundus autofluorescence have been reported in DME and this could be explained by the accumulation of oxidative products induced by activated microglial cells [31][32][33] .…”
mentioning
confidence: 99%